KHR. AS'AD SYAMSUL ARIFIN'S DA'WAH STRATEGY IN CONQUERING THE RASCALS IN SITUBONDO DISTRICT - fikri riswandha cahya (Indonesian Journal of Islamic Communication, 2024)
This article examines KHR's Da'wah Strategy. As'ad Syamsul Arifin in Conquering Rogues in Situbondo Regency. As in general, "black" circles or what are usually called bromocorah, bastards, bandits and so on, are almost always looked down upon. The "bad" stigma that is built up based on their behavior can at least be said to be far from good or positive things. Kiai Sukorejo saw this as an opportunity that he could use to broadcast the Islamic boarding school and fight to defend the country at that time. This research is library research which in terms of the type of data sought is also said to be qualitative research. Library research is a series of activities related to methods of collecting library data, reading and taking notes and managing research materials. The da'wah strategy used by Kiai As'ad in conquering the bastards is the Tilawah Strategy (communication strategy), Tazkiyyah Strategy (cleaning attitude and behavior strategy), and Ta'lim strategy (Education Strategy)